Pembentukan Dana Cadangan Pemilihan Kepala Daerah Serentak Tahun 2024 : Studi Di Kabupaten Pekalongan - Karmanis Karmanis; Sugiyanto Sugiyanto; Sumarmo Sumarmo; Murdiansyah Murdiansyah (Universitas 17 Agustus 1945, 2023)
The direct election of a regional head will produce a regional head and deputy regional head who are qualified, competent and have integrity, according to democratic ideals and the will of the people. In comparison with the pattern of electing regional heads through the election of the Regional People's Representative Council, the pattern of electing regional heads directly requires a lot of funds, the regional government must prepare as well as competing candidates as participants. This study examines the Formation of Reserve Funds for the 2024 Simultaneous Regional Head Elections in Pekalongan Regency, using a qualitative method. The author finds that the Regional Regulation concerning the Establishment of Reserve Funds for the 2024 Concurrent Regional Head Elections is urgently needed, because the costs of holding Regional Head Elections are quite large and need to be budgeted for more than one fiscal year, a Reserve Fund is needed, the budgeting of which is allocated for two years.